السبك الصوتي في كتاب (المنثور البهائي) (Journal of the College of Basic Education, 2022)
Active in the fourth century AH, a type of literary writing, which is the solution of drafting and this art is based on the demolition of the poetic text, and rebuilding it in the form of prose text, the poetic text, and this type of prose, defies standing between poetry and prose. One of the most important references for this art is the book ((AL-Manthwr AL-Bhayi)) for AL-Nirmany, and in which he drew for himself aunique approach to composition.Other than the approach of those who preceded him, he reproduces his artistic prose, and then the poetry that he chooses to his prose.In this paper, we try to find the aspects of sonic casting at the levels of solution for mulation, by comparing of poetry and his prose